The New Model: Green Innovation Modified to Moderate the Influence of Integrated Reporting, Green Intellectual Capital toward Green Competitive Advantage - Rachmawati, Sistya (International Journal of Energy Economics and Policy, 2023)
The purpose of this study is to analyze (1) The effect of integrated reporting and green intellectual capital on green competitive advantage, (2) Green innovation moderates integrated reporting and green intellectual capital on green competitive advantage. Quantitative research methods use secondary data, content analysis. The population in this study are companies that publish Annual Reports that have been audited by independent auditors and Sustainability Reports of companies listed on the Indonesia Stock Exchange in 2016-2020 and are taken from IDX-IC. Through purposive sampling method, panel data a combination of cross-section data and time series data, were obtained as many as 324 observations. Data processing using software eviews with Moderated Regression Analysis. The results of this study indicate that integrated reporting and intellectual capital have a significant positive effect on green competitive advantage. Green innovation significantly strengthens the effect of integrated reporting on green competitive advantage. However, green innovation weakens the effect of green intellectual capital on green competitive advantage. The green innovation modified variable which is the novelty of this study has more robustness than the model without novelty.